Pengaruh Model Pembelajaran CORE (Connecting, Organizing, Reflecting, Extending) Terhadap Kemampuan Berpikir Kritis Peserta Didik Dalam Pembelajaran Pendidikan Pancasila (Studi Kuasi Eksperimen di Kelas VII SMP Negeri 2 Cimahi Tahun Ajaran 2024/2025): Penelitian - Rosdiana, Irna; Sapriya; Pitria Sopianingsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study was motivated by the low critical thinking skills of students in Indonesia, particularly in Pancasila Education. The study aimed to determine the effect of the CORE (Connecting, Organizing, Reflecting, Extending) learning model on the critical thinking skills of seventh-grade students in Pancasila Education. The research method used was quantitative with a quasi-experimental design, involving two groups: an experimental class taught using the CORE model and a control class using conventional teaching methods. Data were collected through pre-tests, post-tests, questionnaires, observations, and documentation, then analyzed using normality tests, homogeneity tests, N-Gain tests, and t-tests with the assistance of SPSS version 30. The results of the study indicate that the CORE learning model significantly influences the improvement of students' critical thinking skills, with a significance value of 0.037 < 0.05. Additionally, the questionnaire results show positive responses from students toward all stages of the CORE model. Therefore, the CORE model is effective for enhancing critical thinking skills in Pancasila Education learning at the seventh-grade level of junior high school.